Urticaria multiforme in a child with SARS-CoV-2 infection - Konrad Zawadka; Agnieszka Ołdakowska (PAGEPress Publications, 2021)
We present a case of a 10-month-old boy with urticaria multiforme in the course of coronavirus disease 2019 (COVID-19). Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) contributes to skin lesions in both children and adults. The main cutaneous manifestations of this infection include pseudochilblains, urticaria and maculopapular eruptions. Urticaria multiforme is a common yet underrecognized exanthem in children that is precipitated by viral infections among other causes.